Filling Members of the Financial Audit Board: Constitutional Review and Legislative Intervention - Mutawalli, Muhammad; Masum, Ahmad; Aidonojie, Paul Atagamen; Adebayo, Adesoji Kolawole (Institut Agama Islam Negeri Kendari, 2024)
This article aims to at least outline and analyze the main problem, namely related to the development of an independent system for filling the positions of BPK members according to the theory of independence of state institutions reviewed through constitutional interpretation in the Law. This research is qualitative research with normative juridical methods. Research was carried out using a legal approach, a conceptual approach and a philosophical approach to the issues raised. In this paper, the author applies techniques for collecting legal materials or data, through documentation or literature studies which are carried out by reading, reviewing, classifying, identifying and understanding legal materials in the form of regulations and books and literature. which is related to the research object discussed in this paper. The analysis of legal materials used applies qualitative, descriptive and prescriptive methods that are oriented towards answering problem formulations. Apart from that, analysis of legal materials also focuses on the inventory aspect of legal materials in the form of soft files and hard files. Manual inventory is carried out on hardfile legal materials, while digital inventory is carried out on legal materials in softfile form. After the inventory, an analysis process is carried out with reference to the legal issues and discussion formulations raised. The finding in this paper is that there is polarization in filling the positions of BPK members which is far from the principle of independence and also prioritizes the supervisory aspect in filling these positions so that the principle of checks and balances is not implemented within the BPK itself. The polarization of filling the positions of BPK members which seems political has resulted in hidden interests which could actually disrupt the independence of the BPK as a state audit institution. In the future, it is necessary to strengthen the BPK institution as a state institution that is in a new space of power known as the inspection space by making changes and additions to concrete and internal regulations in the aspect of filling out BPK members in terms of the theory of state institutional independence